The Urgency of Establishing a Special Narcotics Court in Indonesia: A Comparative Study with the United States, Australia and Scotland - Amelda Yunita; Topo Santoso; Firman Muntaqo; Ruben Achmad (Universitas Muhammadiyah Purwokerto, 2026)
The high number of narcotics crimes every year shows that narcotics crimes, especially narcotics abuse, are a serious threat to the lives of the Indonesian people. The practice of law enforcement against narcotics abusers in Indonesia that prioritizes the imposition of criminal sanctions in prison has proven that the penal approach has failed. The urgency of establishing a Special Narcotics Court to combat narcotics crimes is the primary focus of this article, which draws lessons from the United States, Australia, and Scotland, all of which already have special narcotics courts with various systems. This paper is the result of doctrinal law research using a statutory approach and a comparative approach. Research has found that in the United States and Australia, there are Drug Courts, which are special courts. These courts were established in each state. Meanwhile, Scotland incorporates narcotics handling into the public justice system by using a rehabilitation approach to handling narcotics. The establishment of narcotics courts in Indonesia is critical to be carried out, considering that narcotics abuse can weaken Indonesia's national resilience, and the increasing number of narcotics cases results in overcrowding in correctional institutions. Narcotics crimes also have special characteristics, both in terms of the nature of the crime and the characteristics of the subject of the law, thus further emphasizing the importance of the narcotics court.